Gestión administrativa y su ejecución laboral de las secretarías del Gobierno Autónomo Descentralizado del cantón Baba - Rizzo Huacón, Jessica Tahys (2021)
This case study was carried out with the purpose of determining the administrative management and their labor execution of the secretaries in the decentralized autonomous government of the Baba canton, since administrative management is essential to start any administrative process within an institution or organization. In the same way, labor execution is important for the productivity and efficiency of administrative activities, that is why secretaries must be in continuous training to improve the functionalities of the establishment. To carry out this research project, surveys were used as a technique, which were used by the secretaries of the institution, where key questions were formulated to obtain adequate information about the research topic, this with the purpose of collecting all the necessary information, and in such a way to reach a conclusion that allows to identify the problems and give them solutions, in order to improve the development of the establishment. In the development of this research, it was possible to show the problems that affect the development of the Decentralized Autonomous Government of the Baba Canton, one of them being the deficiency in the administrative processes due to lack of knowledge of the secretaries, and on the other hand also, their scarce application of secretarial techniques, causing the delay in the professional productivity of the members of this institution.